Prediction of Pinus rudis Endl. production and yield in Aloapan, Oaxaca - Magaña Torres, Octavio S.; Torres Rojo, Juan Manuel; Rodríguez Franco, Carlos; Aguirre Díaz, Heriberto; Fierros González, Aurelio M. (Instituto de Ecología, A.C., 2016)
The development of equations to predict yield and production of Pinus rudis Endl. is described. The data for model development were obtained from two measurements of a set of permanent plots located in Aloapan, Oaxaca. The prediction model is a whole stand model with a projection of diameter classes through the Weibull distribution. Stand´s attributes are predicted with both, explicit and implicit predictions. The explicit prediction is based on modifications to the basal area and volume compatible growth models. The implicit prediction is made by recovering the diameter distribution predicted through the parameter prediction method. All growth models, even those related to the Weibull distribution parameter prediction showed an excellent goodness to fit.